The formed surface characteristics of SiCf/SiC composite in the nanosecond pulsed laser ablation. Issue 24 (15th December 2022) - Zeng, Jiaheng; Zhang, Quanli; Zhao, Jing; Cai, Yibin; Chu, Chenglong; Zhu, Yandan; Xu, Jiuhua
Abstract: For the advantages of high-temperature resistance, corrosion resistance and ultra-high hardness, SiCf /SiC composite is becoming a preferred material for manufacturing aero-engine parts. However, the anisotropy and heterogeneity bring great challenges to the processing technology. In this study, a nanosecond pulsed laser is applied to process SiCf /SiC composite, where the influence of the scanning speed and laser scanning direction to the SiC fibers on the morphology of ablated grooves is investigated. The surface characteristics after ablation and the involved chemical reaction of SiCf /SiC are explored. The results show that the increased laser scanning speed, accompanied by the decreasing spot overlap rate, leads to the less accumulation of energy on the material surface, so the ablation effect drops. In addition, for the anisotropy of the SiCf /SiC material, the obtained surface characteristics are closely dependent on the laser scanning direction to the SiC fibers, resulting in different groove morphology. The element composition and phase analysis of the machined surface indicate that the main deposited product is SiO2 and the carbon substance. The results can provide preliminary technical support for controlling the machining quality of ceramic matrix composites.